Therapeutic Effect of Yijinjing Rehabilitation Training Combined with Interference Current Therapy on Patients with Knee Osteoarthritis - XU Ming; LI Ya; QIN Shuang; LU Xiaoye; AI Kun; ZHANG Hong (康复学报)
ObjectiveTo observe the effect of Yijinjing rehabilitation training combined with interference current therapy (ICT) on motor function and balance function of patients with knee osteoarthritis (KOA).MethodsA total of 68 patients with KOA in the Rehabilitation Medicine Department of Changsha Central Hospital from April 2022 to January 2023 were randomly divided into control group and observation group, with 34 cases in each group. During the intervention, two cases discontinued the trial or dropped out respectively in the control group and observation group, and a total of 64 cases were finally included, 32 cases in each group. Both groups received routine rehabilitation treatment. The control group received ICT on treatment additionally, with the carrier frequency of 4 000 Hz and the beat frequency of 90-100 Hz based on the tolerance of patients, once a day, 20 minutes a time, six times a week, lasting for four weeks. The observation group received additional Yijinjing rehabilitation training on the basis of the control group to ensure that the patients could complete 50% or more rehabilitation training, without pain or with slight pain, once a day, 20 minutes a time, six times a week, lasting for four weeks. Before and after treatment, visual analogue score (VAS) was used to evaluate the severity of pain; universal goniometer was used to measure the active range of motion (AROM); timed "up and go" test (TUGT) was used to evaluate the functional walking ability; Western Ontario and McMaster University Arthritis Index (WOMAC) score was used to evaluate knee function; and Berg balance scale (BBS) and balance function test system were used to evaluate balance function (left and right swing index, center of gravity track length, track rectangular area, track peripheral area, and track length per unit area with eyes open or closed).ResultsCompared with that before treatment, TUGT, pain, stiffness and physical function scores and total score of WOMAC, left and right swing index, center of gravity track length, track rectangular area and track peripheral area with eyes open or closed in both groups after treatment decreased significantly, the proportion of low VAS score (0-2 points), the maximum AROM, the BBS score and track length per unit area with eyes open or closed increased significantly, and the differences were statistically significant (P<0.05). Compared with the control group, TUGT, pain, stiffness and physical function scores and total score of WOMAC, left and right swing index, center of gravity track length, track rectangular area and track peripheral area with eyes open or closed in the observation group after treatment decreased significantly, the proportion of low VAS score (0-2 points), the maximum AROM, the BBS score and track length per unit area with eyes open or closed increased significantly, and the diffe-rences were statistically significant (P<0.05).ConclusionYijinjing rehabilitation training combined with ICT can improve pain, motor function and balance function of patients with KOA, which is recommended for clinical application.